Pengembangan Aplikasi DESDM Pada Sub Bagian Tata Usaha Dinas Energi dan Sumber Daya Mineral Provinsi Jawa Timur - Damayanti, Adinda Putri; Gamaputra, Gading (Universitas Negeri Surabaya, 2024)
This research was motivated by archive’s system at Sub-Section of Administration of the Energy and Mineral Resources Department of East Java Province which is still carried out manually, in the arrangement and storage of archives are not in alphabetical order and year, some archive’s cover are torn, damaged, and not same between odner’s each other, and some of information’s archive on the folder is not ordered by date of letter or number’s letter. Therefore, the researcher developed a DESDM archival application using Waterfall method with Microsoft Excel as basic application and Visual Basic for Application (VBA) as the programming language. The result of the testing application got a positive response and has be potential to be used in the future.